Respuesta :
distributive property is a(b+c)=ab+ac
so
-(x+2)=-1(x+2)=-1(x)-1(2)=-x-2
5(2x-5)=5(2x)+5(-5)=10x-25
you get
1-x-2+2x=10x-25-x
answer is B
We want to apply the distributive property to the given expression.
The correct option is B:
1 - x - 2 + 2x = 10x - 25 - x
Let's see how to solve this:
Remember that the distributive property says that:
A*(B + C) = A*B + A*C.
Here we have the expression:
1 - (x + 2) + 2x = 5*(2x - 5) - x
We can apply the distributive property to the first term in the right side, we will get:
1 - (x + 2) + 2x = 5*(2x - 5) - x
1 - (x + 2) + 2x = 5*2x - 5*5 - x
1 - (x + 2) + 2x = 10x - 25 - x
Now we can also apply the distribute property to the second term in the left side:
1 - (x + 2) + 2x = 10x - 25 - x
1 - x - 2 + 2x = 10x - 25 - x
Then the correct option is B.
If you want to learn more, you can read:
https://brainly.com/question/5637942